Academic recovery : supporting students in academic probation - Dial, Michael T., 1986- (National Resource Center for The First-Year Experience® and Students in Transition, 2022)
"An academic resource for higher education professionals that provides guidance on how to better support students who are in endanger of or are on academic probation."--